Respuesta :
Answer:
f(5) = 3200
Step-by-step explanation:
Using the recursive formula to generate the terms, that is
f(2) = 2 × f(1) = 2 × 200 = 400
f(3) = 2 × f(2) = 2 × 400 = 800
f(4) = 2 × f(3) = 2 × 800 = 1600
f(5) = 2 × f(4) = 2 × 1600 = 3200
Answer: 6400
Step-by-step explanation:
Given :
f(1) = 200
f(n) = 2.f(n-1) , for n = 2 ,3 , 4 , ...
To find the 5th term
when n = 2 , the sequence becomes
f(2) = 2 .f(2-1)
f(2) = 2 f(1)
since f(1) = 200
therefore:
f(2) = 2 x 200
f(2) = 400
When n = 3
f(3) = 2f(2)
f(3) = 2 x 400
f(3) = 800
When n = 4
f(4) = 2 f(3)
f(4) = 1600
When n =5
f(5) = 2f(4)
f(5) = 3200
When n = 6
f(6) = 2f(5)
f(6) = 6400
Since n = 2 , 3 , 4 ... this means that the 5th term if f(6) , therefore ,the 5th term is 6400